Single-cell integrated transcriptomics reveals the role of keratinocytes in head and neck squamous cell carcinoma - Shaokun Liu; Meng Lian; Boxuan Han; Jugao Fang; Zhenlin Wang (Journal of Applied Genetics, 2024)

Triple-crosslinked double-network alginate/dextran/dendrimer hydrogel with tunable mechanical and adhesive properties: A potential candidate for sutureless keratoplasty - Wen Zhang; Shujing Liu; Lixiang Wang; Boxuan Li; Mengzhen Xie; Yingping Deng; Jialuo Zhang; Huazhang Zeng; Li Qiu; Lisha Huang; Tao Gou; Xiaobo Cen; et al. (Carbohydrate Polymers, 2024)

Simultaneous nitrification and denitrification in a hybrid activated sludge-membrane aerated biofilm reactor (H-MABR) for nitrogen removal from low COD/N interflow: A pilot-scale study - Hengyi Liu; Lei Li; Wenjie Ye; Boxuan Zhao; Yun Peng; Guotao Liu; Xiaofeng Gao; Xuya Peng (Journal of Environmental Management, 2024)

Impacts and influencing pathways of urbanization on carbon–water-energy-food nexus across Chinese cities - Chenggang Li; Yong Liu; Zhenci Xu; Gang Zhao; Youhui Bao; Chengcheng Cai; Yu Lu; Yufeng Mao; Alexander Boxuan Wang; Liang Wu (Environment, Development and Sustainability, 2024)
Food, water, energy and carbon (F-W-E-C), as important factors of urban development, have synergistic effects and trade-off effects with each other. Scientifically assessing the impact of urbanization on the F-W-E-C nexus is beneficial to optimize the urban development layout and achieve the sustainable urban development. Nevertheless, extant studies have not evaluated the impact and influencing pathways of urbanization on the F-W-E-C nexus. In this study, the Coupling Coordination Degree Model is used to explore the F-W-E-C nexus of 252 prefecture-level cities in China. The panel data model and mediating effect model are utilized to study the impact of urbanization on the F-W-E-C nexus and the impact pathways. This study finds that the F-W-E-C nexus across Chinese cities is weak trade-off. The urbanization promotes the synergy of F-W-E-C. The positive impact is greater in the central cities than in the eastern and western cities, and is greater in medium-sized cities than in small cities, large cities and above. The technological progress is an important pathway of urbanization impacting the F-W-E-C nexus, and assists urbanization to generate a positive influence on the F-W-E-C nexus. This research has implications for promoting a systematic, orderly, and rational coordination development of F-W-E-C and for sustainable urbanization development in China and the world.

CD8 + T cell response in QuantiFERON-TB Gold Plus testing was associated with tuberculosis recurrence: a 2-year prospective study - Henan Xin; Xuefang Cao; Boxuan Feng; YiJun He; Tonglei Guo; Jiang Du; Lingyu Shen; Yuanzhi Di; Zisen Liu; Dakuan Wang; Bin Zhang; Zhanjiang Zhang; et al. (Infectious Diseases, 2024)

Vertically designed high-performance and flexible thermoelectric generator based on optimized PEDOT:PSS/SWCNTs composite films - Binjie Xia; Xiao-Lei Shi; Li Zhang; Jia Luo; Wen-Yi Chen; Boxuan Hu; Tianyi Cao; Ting Wu; Wei-Di Liu; Yanling Yang; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2024)

Seasonal variations of microplastics in surface water and sediment in an inland river drinking water source in southern China - Wenyu Zhao; Jing Li; Mengyue Liu; Rui Wang; Boxuan Zhang; Xiang-Zhou Meng; Shengwei Zhang (Science of The Total Environment, 2024)